Evaluation of first-line therapies for the treatment of candidemia in ICU patients: A propensity score analysis. (April 2020) - Bienvenu, Anne-Lise; Pradat, Pierre; Guerin, Claude; Aubrun, Frederic; Fellahi, Jean-Luc; Friggeri, Arnaud; Guichon, Céline; Hernu, Romain; Menotti, Jean; Monard, Céline; Paulus, Sylvie; Rimmele, Thomas; et al.
Highlights: Echinocandins recommended for candidemia and fluconazole, as an alternative. Emergence of Candida resistance to echinocandins. Local guidelines for candidemia according to clinical practice and local epidemiology. Fluconazole suggested to be a reasonable alternative to echinocandins in ICU. To be incorporated in local guidelines through antifungal stewardship activities. Abstract: Background: Candidemia is a major cause of mortality in the intensive care unit (ICU). According to the Infectious Diseases Society of America (IDSA), an echinocandin is recommended as initial therapy and fluconazole as an alternative. In a context of echinocandin resistance development, the question arising is whether azoles are a suitable alternative to echinocandins for the treatment of candidemia in critically ill patients. Methods: A 3-year (2015–2017) retrospective multicentric cohort study was conducted. Adult patients with a diagnosis of candidemia during the ICU stay and treated with echinocandins or azoles were included. Demographic, clinical data, mycological data, and antifungal treatments were collected. Kaplan–Meier survival analysis, univariate analysis, and a multivariate logistic regression analysis using a propensity score with the inverse probability of treatment weighting method were performed. Findings: Seventy-nine patients (n = 79) were analyzed. Treatment success, as well as survival on day 90 (Kaplan–Meier survival analysis, log rank test, p = 0.542), were comparable between patients who received echinocandins (caspofungin (n = 47)) or azoles (fluconazole (n = 29) or voriconazole (n = 3)). A multivariable analysis demonstrated that higher SOFA score on the day of candidemia diagnosis and absence of adequate Candida source control were independently associated with a greater risk of 90-day mortality, whereas azoles treatment was not associated with an excess 90-day mortality. Interpretation: This study confirms that the use of azoles recommended for candidemia, mostly fluconazole, as a first-line therapy is a reasonable alternative to caspofungin for ICU patients in our institution. This needs to be included in local guidelines through antifungal stewardship programs.